Cognitive, Affective, and Conative Attitude of Farmers to Rice Farming Insurance (RFI) Program in Tanah Datar District, West Sumatera Province, Indonesia - Siska Handayani; Rudi Febriamansyah; Mahdi Mahdi (International Journal of Agricultural Sciences, 2019)
The Ministry of Agriculture has implemented the Rice Farming Insurance (RFI) Program in Indonesia since 2015 to protect farmers from possible loss of crop failure due to various potential disasters such as floods, drought, pests, etc. Although it has been immensely encouraged by the relevant field agencies, this RFI program was unsuccessful. The land area that follows the RFI program in Tanah Datar District decreased significantly from 1,061 Ha (2016) to about 150 Ha (2017), of the total target area of 2,300 Ha. This study is conducted to find factors that lead to decreased farmer participation in this RFI program, mainly by studying how the government has done the socialization process and how farmers' actual attitude towards this RFI program? By applying qualitative and quantitative approaches, this study obtained the empirical facts that the socialization process, done by relevant stakeholders, including government, private and community leaders, and farmers, not so intensified. The attitude of farmers to this program showed that, in the cognitive aspects, most farmers in all five categories still do not fully understand and confident about the RFI program. It is similar to their affective elements; most farmers in the five categories have not yet determined attitudes, whether they like or dislike the RFI program. Meanwhile, only in terms of their conative aspects, mostly farmers of all categories are eager to learn more and become the RFI program participant.